Transcriptome analysis revealed the roles of long non-coding RNA and mRNA in the bursa of Fabricius during pigeon (Columba livia) development - Wang, Xun; Wu, Jie; Hu, Silu; Peng, Qiyi; Yang, Fuxing; Zhao, Ling; Lin, Yu; Tang, Qianzi; Jin, Long; Ma, Jideng; Guo, Hongrui; Tang, Huaqiao; et al. (Frontiers in Immunology, 2022)
The bursa of Fabricius (BF) is the critical humoral immune organ to birds, playing an essential role in B lymphocyte differentiation. However, unlike other poultries, surgical removal of pigeon BF did not limit humoral immune responsiveness. To investigate the expression profiles and the potential role of mRNA and long non-coding RNA (LncRNA) in squab BFs, transcriptome analysis was performed by RNA-Sequencing (RNA-Seq) over three developmental stages (1-day, 13 and 26 days old). We identified 13,072 mRNAs and 19,129 lncRNAs, of which 2,752 mRNAs and 1,515 lncRNAs were differential expressed (DE) in pigeon BFs over three developmental stages. Cluster analysis presented different expression patterns in DE mRNAs and lncRNAs. Functional enrichment analysis revealed that DE lncRNAs and mRNAs with distinct expression patterns might play crucial roles in the immune system process and tissue morphogenesis. In particular, some DE genes and lncRNAs with higher expression levels in 13D or 26D are related to lymphocyte activation and differentiation, adaptive immune response, positive regulation of immune response, leukocyte migration, etc. Protein-protein interaction (PPI) network and Molecular Complex Detection (MCODE) analysis sreened six significant modules containing 37 genes from immune-related DE gene cluster, which is closely linked in B cell activation, lymphocyte differentiation, B cell receptor signaling pathway, etc. Our study characterizes mRNA and lncRNA transcriptomic variability in pigeon BFs over different developmental stages and enhances understanding of the mechanisms underlying physiological functions of pigeon BF.